DICTIONARIES OF FOREIGN WORDS OF THE RUSSIAN LANGUAGE: EVOLUTION OF DEVELOPMENT (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article examines the issue of comparing different editions of dictionaries of foreign words in the Russian language. In particular, a comparative description of their lexical composition is given, indicating the predominant groups of units. Semantic transformations characteristic of foreign words undergoing the stage of adaptation in the Russian language are also described.